2018
DOI: 10.22146/mot.28533
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Stability Test of SNEDDS (Self-nanoemulsifying Drug Delivery System) and Nanoemulsion Ethyl Acetate Fraction of Garcinia mangostana L.

Abstract: The mangosteen peels (Garcinia mangostana L.) has high free radical scavengers activity. This study aims to determine the physical and chemical conditions that are formulated in SNEDDS and nanoemulsion preparations. SNEDDS was made with various concentrations of Tween 80, PEG 400, and Virgin Coconut Oil (VCO) with a ratio of 4,98:1,02:1. Nanoemulsions were made with the addition of water to SNEDDS. Stability observation results were analyzed by statistics. The results of physical stability test show that all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 5 publications
0
12
1
6
Order By: Relevance
“…Mixtures of extract and oil were stored at 26–27°C for 5 days to visually observe the presence of undissolved extract in oil. Solubility data of mangosteen extract in VCO, reported by Pratiwi et al [ 17 ], was available for comparison purposes.…”
Section: Methodsmentioning
confidence: 99%
“…Mixtures of extract and oil were stored at 26–27°C for 5 days to visually observe the presence of undissolved extract in oil. Solubility data of mangosteen extract in VCO, reported by Pratiwi et al [ 17 ], was available for comparison purposes.…”
Section: Methodsmentioning
confidence: 99%
“…This value can improve the decreasing of surface tension between oil and water. PEG 400 as co-surfactants can increase the surface fluidity through penetration way to surfactants film that can create a free space between the surfactants molecules (Pratiwi et al, 2018). Nanoemulsion of ethanolic mangosteen leaves extract can be shown on Figure 1.…”
Section: Formulation Of Self Nanemulsifying Drug Delivery System (Snedds)mentioning
confidence: 99%
“…The surface charge of nanoemulsion with nonionic surfactant comes from the adsorption of ions in the water phase or due to droplets friction with its dispersing medium. The adsorbed ions on the droplets surface produce an electric double layer resulting a repulsive force among the particles, thus it prevents aggregation [42]. Moreover, dye test showed that all ginger oil nanoemulsions type were O/W ( Figure 6).…”
Section: Characterization Of Optimum Nanoemulsion Formulasmentioning
confidence: 99%
“…It was characterized by uniform dispersion of methylene blue mainly in water phase. O/W nanoemulsion with nonionic surfactant results a film layer on the droplets surface preventing droplets integration in the dispersing medium [42].…”
Section: Characterization Of Optimum Nanoemulsion Formulasmentioning
confidence: 99%